PENGARUH KOMPETENSI DAN EFIKASI DIRI TERHADAP KINERJA KARYAWAN DI DEPARTEMEN QUALITY CONTROL PADA PT DELLIFOOD SENTOSA CORPINDO KOTA TANGERANG - Riawan, Sigit; Amelia, Rizka Wahyuni (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of competency and self-efficacy on employee performance in the Quality Control department at PT Dellifood Sentosa Corpindo, Tangerang City. The data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, correlation coefficient, simple linear regression, multiple linear regression, coefficient of determination and hypothesis testing. The results of this research are partially proven by the simple linear regression equation Y = 21.688 + 0.464 contribution to Employee Performance (Y) was 20.9% while 79.1% was influenced by other variables not examined in this research. Partial hypothesis testing for the Competency variable (X1) obtained a value of tcount > ttable (4.738 > 1.988). This is reinforced by a significance value of 0.000 < 0.005, which can be concluded that H0 is rejected and H1 is accepted, which means that Competence has a significant influence on Employee Performance. The results of this research are partially proven by the simple linear regression equation Y = 15.100 + 0.619 X1, with a correlation coefficient of 0.600, meaning that the two variables have a strong level of relationship. The determination value is 0.360, which means that the Self-Efficacy variable (X2) contributes to Employee Performance (Y) by 36%, while 64% is influenced by other variables not examined in this research. The research results were proven simultaneously with the multiple linear regression equation Y = 11.844 + 0.180 X1 + 0.516 The determination value is 0.381, which means that the Competency (X1) and Self-Efficacy (X2) variables contribute to Employee Performance (Y) by 38.1%, while 61.9% is influenced by other variables not examined in this research. Simultaneous hypothesis testing obtained a value of Fcount>Ftable or (25,881 > 3.11), this was confirmed by a significance value of 0.000 <0.005. So it can be concluded that H0 is rejected and H3 is accepted, meaning that Competence and Self-Efficacy are simultaneously significant to Employee Performance.